БИОПЛАЗМА, БИОГОЛОГРАФИЧЕСКИЕ ОСОБЕННОСТИ ТОЧЕК АКУПУНКТУРЫ И«ЭФФЕКТ КИРЛИАН» (Experimental biology, 2015)
The principle of biogeography (and chronothomogroghic) reflection in the acupunting points AP of the events motion and direction motion and direction in the nines health determinate fly the Kirilian nuthatch (plasmographia) had been discussed. Phautome shapes of infections and past, present and future pathologic states appirienced Condensed of theanamnesis and katamnesis data with virtual data (ψ-hologram’s) mashes possible to consider AP as the bioenergetics formations which Keep holographic information a font destructive proprieties of bioplasma macro and micro topologic psychosomatic health state influencing
Keywords: ψ-hologram’s; chronothomogroghic; plasmographia